Transforming Student’s Arabic Writing Skills through Word Square Media: Examining its Effectiveness - Siti Soleha; Evi Muzaiyidah Bukhori; Mokhammad Miftakhul Huda (UIN Syekh Wasil Kediri, Indonesia, 2024)
This study aims to examine the effectiveness of Word Square media in improving students’ Arabic writing skills. Writing in Arabic requires structured, engaging, and student-centered learning strategies to enhance learners' outcomes. However, traditional methods often fail to stimulate students’ interest and competence in Arabic writing. This quantitative research employed a one-group pretest-posttest experimental design involving 22 eleventh-grade students. Data were collected through writing tests administered before and after the implementation of Word Square media. The objective was to measure the extent to which the media could enhance students’ writing performance. Descriptive statistics showed a substantial improvement in students’ average scores from 66.05 in the pretest to 81.77 in the posttest. There were also consistent increases in minimum, maximum, and standard deviation values. The Shapiro-Wilk test indicated normal data distribution with significance values of 0.584 (pretest) and 0.147 (posttest), both greater than 0.05. The paired sample t-test showed a significance value (2-tailed) of 0.000, which is less than 0.05, indicating a statistically significant difference between pretest and posttest scores. The findings confirm that Word Square media is effective in enhancing students’ Arabic writing skills. The media enables students to engage in learning interactively, enjoyably, and collaboratively. Thus, Word Square can be considered a valuable instructional tool to be integrated into Arabic language learning to boost students’ writing performance.